Winning habits : how elite equestrians master the mental game - Paterakis, Annette, 1985- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"A unique and groundbreaking analysis of how to succeed in equestrian sport, this book unpacks the winning habits of successful equestrians to form a toolkit for readers to develop their own winning habits. Applying psychological understanding in peak performance, this book is bolstered by interviews with top contemporary professional showjumping athletes to explore and show how leading equestrians have interpreted various methods and built them into approaches for their own training. Theoretical concepts such as mindset, deliberate practice, focus and flow are broken down and translated into practical steps for a more powerful and effective way of thinking, training and performing. Renowned equestrian mental coach Annette Paterakis reveals factors of success, as well as answers common questions, from building lasting confidence to responding to failure. Smashing the myths of talent and hard work, Paterakis offers a refreshing take on mindset, focus and approach to success both in and out of the show ring. An essential read for anyone who would like to learn or improve their mental game, this book is uniquely suited for equestrian riders, coaches, and other athletes, as well as supplementary reading for applied sport psychology courses"--
Keywords: Horse sports; Horse sports -- Psychological aspects; Horsemen and horsewomen -- Trainig of; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology; SPORTS & RECREATION / General